Dark Lord of Derkholm - Jones, Diana Wynne (London : HarperCollins Children's Books, 2013)
Derk, an unconventional wizard, and his magical family become involved in a plan to put a stop to the devastating tours of their world arranged by the tyrannical Mr. Chesney.
Young Adult.
Young Adult
Keywords: Fantasy; Magic -- Fiction; Wizards -- Fiction; Magic -- Fiction; Wizards -- Fiction; Fantastic fiction